Academic mobility of students in the context of educational internationalization - Vovchasta, Nataliia; Dobrovolska, Lesia; Melnik, Svetlana; Piekharieva, Alona; Vasenko, Valentyna; Dziurakh, Yurii (My University, 2022)
An internationalization process is holistically aimed at creating a single educational space for education applicants, so they will have access to high-quality professional education regardless of the economic and social level of their home country's development. Academic mobility of education applicants is a key condition for the educational internationalization principle’s implementation. This article examines the academic mobility features of both foreign education applicants and Ukrainian students who want to study at foreign universities. Academic mobility development in the educational internationalization context contributes to economic growth and country development, ensures that higher professional education is taken to a new quality level, which will attract applicants from other countries
Academic mobility of students in the context of educational internationalization / Nataliia Vovchasta, Lesia Dobrovolska, Svetlana Melnik, Alona Piekharieva, Valentyna Vasenko, Yurii Dziurakh, // Ad Alta. Journal of interdisc iplinary research, 2022. – Vol. 12, – Issue 1, (special issue XXVI). –P. 82–89.
Keywords: academic mobility, higher professional education, internationalization of education, foreign students, education applicants; академічна мобільність, вища освіта, інтернаціоналізація освіти, іноземні студенти, освітні програми.